Proposal writing guidebook the complete guide to writing winning and successful proposals for funding by funding agencies - Pineda, Danilo D. (Metro Manila Tritium Knowledge Center Pub., 2002)
Purpose: "...tells [you] the step-by-step procedures, techniques, and strategies in writing [your] proposals."
Content/s: Terms used in Proposal Writing. Nonprofit Non-stock Organization. Background Information. Components of Proposal. Project Presentation. Budget. Organizational Information. Proposal Conclusion. Writing Suggestions. Funding Proposal. List of International Funding Agencies.
Keywords: Proposal writing for grants -- Philippines -- Handbooks, manuals, etc; Nonprofit organizations -- Finance -- Handbooks, manuals, etc